The placenta height. I macroscopic characteristics and morphometry - Kadar, Katalin (2015)
The authors have studied newborn weight and placentas pregnancies from Puno, Peru at an altitude of 3850 m.; as studied 46 normal pregnancies from different hospitals in from 46 normaI control group they Lima at 150 m. The newborn weights were similar in both places, however, placental weight and volume were higher in Puno, so the placental coefficient was higher in altitude. The macroscopic analysis in terms of parenchimal and non parenchimal tissue was not different in both groups, but the microscopic analysis showed richer capillarity with diminished villous in Puno. No differences were appreciated in the proportion of trophoblastic ephithelium. The total area of the chorial villous and capillary surface were significantly major in altitude. The authors postulate these morphologic changes favor the metabolic placental exchange in the hypoxic environment of high altitude.